Volume Rendering of Angiographic Optical Coherence Tomography Angiography in Fovea Plana and Normal Foveal Pit - Fragiotta, Serena; Ciancimino, Chiara; Perdicchi, Andrea; de Paula, Alessandro; Abdolrahimzadeh, Solmaz; Scuderi, Gianluca (Frontiers in Neurology, 2021)
This paper aims to study adaptative vascular arrangements in idiopathic fovea plana with volume-rendered optical coherence tomography angiography (OCTA). A retrospective review of two cases of idiopathic fovea plana (mean age: 26.5 years) and two age-matched controls imaged with OCTA was conducted using spectral-domain OCTA (RTVue XR Avanti, Optovue, Inc., Fremont, CA) equipped with the AngioVue software. Both en face OCTA slabs and OCTA b scans were processed through Fiji software (http://fiji.sc; software version 2.0.0-rc-68/1.52e), and then extracted as image sequences for volume rendering reconstructions using the ImageVis3D volume rendering system (3.1.0 release). Eyes with idiopathic fovea plana demonstrated a regular superficial vascular plexus connecting to a single vascular monolayer representing the deeper vascular plexuses. At this location, several vertical short path connections were demonstrated, in contraposition with normal eyes where short path connections were infrequently observed. Advances in three-dimensional OCTA reconstruction increase the understanding of vascular connections and arrangement in retinal plexuses and possible anatomical variations that cannot be detected with conventional two-dimensional b scans.